Faktor Penyebab Kesulitan Siswa SMA Memahami Kesetimbangan Kimia : Literature Review - Yestin Takowa; Julhim S Tangio; Thayban Thayban; Wiwin Rewini Kunusa; Erni Mohamad (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Understanding chemical equilibrium concepts poses significant challenges for high school students due to the topic’s abstract and complex nature. This literature review identifies key factors contributing to these difficulties, including widespread misconceptions, cognitive and pedagogical barriers, and environmental influences such as family support and learning resources. The review highlights the importance of constructivist and cognitive learning theories in designing effective instructional strategies that actively engage students and facilitate deeper conceptual understanding. Furthermore, the integration of educational technologies—such as interactive simulations and virtual laboratories—provides enriched learning experiences that help overcome conceptual misunderstandings. An integrated approach combining innovative teaching methods and technology use is recommended to enhance students’ comprehension of chemical equilibrium. Future research should focus on practical applications of these models and evaluate their effectiveness across diverse educational settings.